Causes and consequences of word structure - Hay, Jennifer (Outstanding dissertations in linguistics., 2003)
This book explores the effect of speech perception strategies upon morphological structure. Using connectionist modelling, perception and production experiments, and calculations over lexical, Jennifer Hay investigates the role of two factors known to be relevant to speech perceptions: phonotactics and lexical frequency. Hay demonstrates that low-probability phoneme transitions across morpheme boundaries exert a considerable force toward the maintenance of complex words, and argues that the relative frequency of the derived form and the base significantly affects the decomposability of comp.